Zinc Oxide Nanoparticles Damage Tobacco BY-2 Cells by Oxidative Stress Followed by Processes of Autophagy and Programmed Cell Death - Balážová, Ľudmila; Baláž, Matej; Babula, Petr (Nanomaterials (Basel, Switzerland), 2020)
Nanomaterials, including zinc oxide nanoparticles (ZnO NPs), have a great application potential in many fields, such as medicine, the textile industry, electronics, and cosmetics. Their impact on the environment must be carefully investigated and specified due to their wide range of application. However, the amount of data on possible negative effects of ZnO NPs on plants at the cellular level are still insufficient. Thus, we focused on the effect of ZnO NPs on tobacco BY-2 cells, i.e., a widely accepted plant cell model. Adverse effects of ZnO NPs on both growth and biochemical parameters were observed. In addition, reactive oxygen and nitrogen species visualizations confirmed that ZnO NPs may induce oxidative stress. All these changes were associated with the lipid peroxidation and changes in the plasma membrane integrity, which together with endoplasmatic reticulum and mitochondrial dysfunction led to autophagy and programmed cell death. The present study demonstrates that the phytotoxic effect of ZnO NPs on the BY-2 cells is very complex and needs further investigation.
Keywords: ZnO nanoparticles; phytotoxicity; oxidative stress; programmed cell death; BY-2 cells; autophagy